Transcriptomic and hormonal dynamics in relation to adventitious rooting of two parental Petunia species highlight a coordinated activation of the jasmonate and auxin pathways and an important role of upper-shoot-derived auxin influx - Jurenic, Ivona; Chamas, Sindy; Nagler, Nicole; Balcke, Gerd Ulrich; Druege, Uwe (Frontiers in Plant Science, 2026)
IntroductionAdventitious rooting of cuttings is a key developmental process for the vegetative propagation of many crops that involves phytohormone-controlled reprogramming and redifferentiation of specific cells in the stem base. The endogenous control of phytohormone action at the whole-plant level is not completely understood.MethodsUsing the genome-sequenced Petunia axillaris and Petunia inflata, we monitored the transcriptome of phytohormone-related genes and phytohormone levels in different cutting sections through a phytohormone-targeted microarray, RT-qPCR, and LC-MS/MS, and analyzed the rooting response to manipulations of auxin levels and transport.ResultsIn the stem base of both species, genes controlling jasmonic acid (JA) biosynthesis, conjugation, and signaling, and encoding transcription factors of the ERF family were already upregulated at 0.5 hours post excision (hpe), followed by increased regulation of auxin-related genes. Accordingly, JA and its physiologically active isoleucine conjugate JA-Ile accumulated transiently at 0.5 hpe, before indole-3-acetic acid (IAA) peaked at 2 hpe. Genes controlling auxin biosynthesis were mostly downregulated, whereas three IAA-leucine-resistant-like genes were strongly upregulated between 0.5 and 2 hpe. P. inflata’s greater rooting capacity compared with P. axillaris was linked to higher stem-base IAA levels (0–72 hpe), resulting in a higher IAA/cytokinin ratio and stronger upregulation of auxin-signaling genes. P. inflata showed a steeper IAA gradient between the leaves and the stem base, which was positively and negatively correlated with leaf salicylic acid and cytokinin isopentenyladenine levels, respectively, and associated with exclusive upregulation of PIN-like genes in the leaves. P. axillaris showed a stronger improvement in rooting with low IAA doses than P. inflata. Blocking polar auxin transport in the upper shoot prevented rooting in both species.DiscussionThe results reveal excision-triggered coordination of jasmonate and auxin pathways in the stem base, interacting with ERF transcription factors, and indicate an important role for upper shoot-derived auxin influx, potentially regulated by salicylic acid and cytokinins. Higher rooting capacity of P. inflata can be explained by the higher IAA level in the stem base. The results indicate important roles of ERF113/114, ILR-like2 and 6, PIN6, PIN-like 1/3, the PINOID gene A4A49_10797, ARF11, and several LBD genes in adventitious rooting of Petunia.